Have Gender Gaps in Math Closed? Achievement, Teacher Perceptions, and Learning Behaviors Across Two ECLS-K Cohorts - Joseph R. Cimpian; Sarah T. Lubienski; Jennifer D. Timmer; Martha B. Makowski; Emily K. Miller (SAGE Publishing, 2016)
Studies using data from the Early Childhood Longitudinal Study-Kindergarten Class of 1998-1999 (ECLS-K:1999) revealed gender gaps in mathematics achievement and teacher perceptions. However, recent evidence suggests that gender gaps have closed on state tests, raising the question of whether such gaps are absent in the ECLS-K:2011 cohort. Extending earlier analyses, this study compares the two ECLS-K cohorts, exploring gaps throughout the achievement distribution and examining whether learning behaviors might differentially explain gaps more at the bottom than the top of the distribution. Overall, this study reveals remarkable consistency across both ECLS-K cohorts, with the gender gap developing early among high achievers and spreading quickly throughout the distribution. Teachers consistently rate girls' mathematical proficiency lower than that of boys with similar achievement and learning behaviors. Gender differences in learning approaches appear to be fairly consistent across the achievement distribution, but girls' more studious approaches appear to have more payoff at the bottom of the distribution than at the top. Questions remain regarding why boys outperform girls at the top of the distribution, and several hypotheses are discussed. Overall, the persistent ECLS-K patterns make clear that girls' early mathematics learning experiences merit further attention.